2017
DOI: 10.2147/cmar.s136818
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, diagnostic challenges, and management strategies in checkpoint inhibitor-related pneumonitis

Abstract: Immune checkpoint inhibitors, including cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death-1 (PD-1) inhibitors, represent an effective treatment modality for multiple malignancies. Despite the exciting clinical benefits, checkpoint inhibition is associated with a series of immune-related adverse events (irAEs), many of which can be life-threatening and result in significant treatment delays. Pneumonitis is an adverse event of special interest as it led to treatment-related deaths in early clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 52 publications
3
146
0
3
Order By: Relevance
“…Pneumonitis is an autoimmune toxicity with a wide range of clinical course, ranging from mild dyspnoea to life-threatening respiratory failure [60], with up to 2% of patients developing severe pneumonitis [38]. Unlike the majority of irAEs, it is less common with anti-CTLA-4 monotherapy than with anti-PD-1 treatment [38,60].…”
Section: Thoracic and Cardiac Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumonitis is an autoimmune toxicity with a wide range of clinical course, ranging from mild dyspnoea to life-threatening respiratory failure [60], with up to 2% of patients developing severe pneumonitis [38]. Unlike the majority of irAEs, it is less common with anti-CTLA-4 monotherapy than with anti-PD-1 treatment [38,60].…”
Section: Thoracic and Cardiac Toxicitiesmentioning
confidence: 99%
“…Pneumonitis is an autoimmune toxicity with a wide range of clinical course, ranging from mild dyspnoea to life-threatening respiratory failure [60], with up to 2% of patients developing severe pneumonitis [38]. Unlike the majority of irAEs, it is less common with anti-CTLA-4 monotherapy than with anti-PD-1 treatment [38,60]. It occurs in up to 5% of patients receiving anti-PD1 and anti-PDL1, while it arises in 10% of patients receiving combination treatment [38,60,61], with higher odds of pneumonitis in non-small cell lung cancer compared with melanoma [61][62][63].…”
Section: Thoracic and Cardiac Toxicitiesmentioning
confidence: 99%
“…However, they are associated with several immune-related adverse events (IRAEs). 1 These adverse events include hypophysitis, thyroiditis, myositis, colitis, dermatitis and pneumonitis; however, organizing pneumonia is not a common IRAE, and review of the literature thus far has only identified one case report of such a reaction. 2 While IRAEs can result in morbidity as well as treatment delay, emerging data indicate that they may also correlate with treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…The median time to onset of pneumonitis was 57 days with a considerable range . The fact that this wide of a range was also observed in additional studies underscores the constant vigilance required to monitor for toxicities at any point during the course of therapy (and even after therapy is completed) [8,9,15,18,19]. Immune checkpoint blockade with anti-CTLA-4 and anti-PD-1 has been shown to be a highly effective combination with U.S. Food and Drug Administration approvals in melanoma and renal cell carcinoma.…”
Section: Pulmonary Toxicity: Review Of Pneumonitis Incidencementioning
confidence: 95%